Data sharing policies in scholarly publications: interdisciplinary comparisons. (1st June 2020) - Tal-Socher, Michal; Ziderman, Adrian
Abstract : Digital sharing of research data is becoming an important research integrity norm. Data sharing is promoted in different avenues, one being the scholarly publication process: journals serve as gatekeepers, recommending or mandating data sharing as a condition for publication. While there is now a sizeable corpus of research assessing the pervasiveness and efficacy of journal data sharing policies in various disciplines, available research is largely piecemeal and mitigates against meaningful comparisons across disciplines. A major contribution of the present research is that it makes direct across-discipline comparisons employing a common methodology. The paper opens with a discussion of the arguments aired in favour and against data sharing (with an emphasis on ethical issues, which stand behind these policies). The websites of 150 journals, drawn from 15 disciplines, were examined for information on data sharing. The results consolidate the notion of the primacy of biomedical sciences in the implementation of data sharing norms and the lagging implementation in the arts and humanities. More surprisingly, they attest to similar levels of norms adoption in the physical and social sciences. The results point to the overlooked status of the formal sciences, which demonstrate low levels of data sharing implementation. The study also examines the policies of the major journal publishers. The paper concludes with a presentation of the current preferences for different data sharing solutions in different fields, in specialized repositories, general repositories, or publishers' hosting area.